THE RELATIONSHIP BETWEEN THE ROLE OF CHRISTIANITY TEACHERS (CT) AND THE COMMUNITY DEVELOPMENT IN PONTIANAK CITY OF WEST KALIMANTAN, INDONESIA - Saderach, Herry (International Journal of Research -GRANTHAALAYAH, 2020)
The aim of this research is to find out the relationship between the role of Christianity Teachers (CT) and the community development in the context of empowering the tribe of Dayak in Pontianak city, west Kalimantan province in Indonesia. This research is a causal study through regression analysis. The population of this study is the elementary, secondary and high schools in Pontianak. There were 89 units of analysis used as the sample who were chosen randomly. Findings indicates that there is positive impact of the role of CT on the community development. This research suggests that a good education on the CT is essential in improving human resources, especially in the success of local government program, aiming to create social, economic, and human rights justices.